Unjust noise - Paul Voice (Etikk i Praksis: Nordic Journal of Applied Ethics, 2009)
In this paper I argue that noise is a significant source of social harm and thoseharmed by noise often suffer not merely a misfortune but an injustice. I arguethat noise is a problem of justice in two ways; firstly, noise is a burden of socialcooperation and so the question of the distribution of this burden arises. And,secondly, some noises, although burdensome, are nevertheless just becausethey arise from practices that are ‘reasonable’. I offer a number of distinctions,between necessary and unnecessary noise, between public and private noiseand between reasonable and unreasonable noise. What justice requires willdiffer according to what kind of noise we consider. My purpose is to give normativeurgency to the problem of noise by understanding certain instances ofit as not merely annoyances and nuisances but instances of injustice.